2014
DOI: 10.5901/jesr.2014.v4n6p313
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on the Role of Guidance and Counselling Programme on Kenyan Secondary School Students’ Career Decision Making

Abstract: The study investigated the Perceptions on the role of guidance and counselling programme on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…For dependant variable (QL&D), seven items were adapted from the study of Wickramaratne (2021). For independent variables, seven items each on career guidance & dialogues from the study of Ibrahim, Aloka, Wambiya, and Raburu (2014), and for team level learning from the study of Carson and Mennenga (2019), eight items on mental model development practices were adapted from the study of LaMere et al (2020). For mediating variable (Attitude to Continuous Learning), eight items were adapted from the study of Hursen (2016) and for moderating variable (talentoriented development), seven were adapted from the study of Rita (2013).…”
Section: Instrumentsmentioning
confidence: 99%
“…For dependant variable (QL&D), seven items were adapted from the study of Wickramaratne (2021). For independent variables, seven items each on career guidance & dialogues from the study of Ibrahim, Aloka, Wambiya, and Raburu (2014), and for team level learning from the study of Carson and Mennenga (2019), eight items on mental model development practices were adapted from the study of LaMere et al (2020). For mediating variable (Attitude to Continuous Learning), eight items were adapted from the study of Hursen (2016) and for moderating variable (talentoriented development), seven were adapted from the study of Rita (2013).…”
Section: Instrumentsmentioning
confidence: 99%
“…The outcome of the findings corroborates with other findings discussed above with a positive significant relationship between school counselling services and academic achievement. Also, Chireshe (2012), Dwyer and McNaughton (2004), Hossain and Faisal (2013), Ibrahim, Aloka, Wambiya and Raburu (2014), Lee, Olson, Locke, Michelson and Odes (2009) and McKenzie, Murray, Prior and Stark (2011) investigated the link between guidance and counselling services and students' achievement in secondary schools. Each study found a positive relationship between the impact of counselling services on students' academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Nigerian context, because of the complexity of its political and socio-economic settings, many challenges are associated with students' negative behaviour in secondary school. The challenges include drug abuse, sexual exploitation, kidnapping, unstable homes, stealing, cultism, truancy (Ibrahim, Aloka, Wambiya & Raburu, 2014;Universal Basic Education Commission, 2010). Mogbo, Obumneke-Okeke and Anyachebelu (2011) opined that recent trends in the education system in Nigeria, such as population explosion, examination malpractice, bullying, poor academic performance, quarrelling and other forms of maladaptive behaviours necessitated the need for effective provision of guidance and counselling services in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Some gender studies have also been carried out on students" awareness towards career guidance in schools. These concluded that most girls did not consider career guidance as an important factor for making career choices (Andrea, 2014;Ibrahim, Aloka, Wambiya & Raburu, 2014). Whereas Parhar et al (2013) presented the view that there was no difference in adequacy of direction and advising among female and male were found regarding career guidance.…”
Section: Literature Reviewmentioning
confidence: 99%